Escherichia coli RNA Polymerase Is the Target of the Cyclopeptide Antibiotic Microcin J25 - Delgado, Mónica A. (American Society for Microbiology, 2001)
Escherichia coli microcin J25 (MccJ25) is a plasmid-encoded, cyclic peptide antibiotic consisting of 21 unmodified amino acid residues. It is primarily active on gram-negative bacteria related to the producer strain, inducing cell filamentation in an SOS-independent way. A mutation causing resistance to MccJ25 was isolated. Genetic analysis indicated that it resided in the rpoC gene, encoding the β′ subunit of RNA polymerase, at 90 min on the E. coli genetic map. The mutation was genetically crossed on to a plasmid containing the wild-type rpoC gene. The presence of the recombinant plasmid conferred complete resistance to otherwise sensitive strains. Nucleotide sequencing of the plasmid-borne, mutant rpoC gene revealed a ACC (Thr)-to-ATC (Ile) change at codon 931, within homology block G, an evolutionarily conserved region in the large subunits of all RNA polymerases. MccJ25 decreased RNA synthesis both in vivo and in vitro. These results point to the RNA polymerase as the target of microcin action. We favor the possibility that the filamentous phenotype induced by MccJ25 results from impaired transcription of genes coding for cell division proteins. As far as we know, MccJ25 is the first peptide antibiotic shown to affect RNA polymerase.